An Islamic University in the West and the Question of Modern Authenticity. - Sinclair, Kirstine (Numen: International Review for the History of Religions, 2019)
The aim of this article is to discuss how Islamic universities in the West facilitate and condition the formation of modern Muslim subjectivities in minority contexts, with an emphasis on the institutions as providers of guidelines for good, Muslim minority life. This is done through a case study of Cambridge Muslim College in the UK. Its values and aims are explored through interviews with the founder and dean, faculty members and students, and through participatory observation. Cambridge Muslim College sees itself as a mediator between Islamic traditions and modern Muslims in the West, and as responsible for engaging in the development of both Muslim minorities and the wider society within which it operates. The questions guiding the study are the following: What role do Islamic universities play in shaping modern Muslim subjectivities in the West? How does Cambridge Muslim College combine understandings of authenticity with preparing their students for professional careers in Britain? The study shows that the understanding of authenticity that is encouraged by college dean Shaykh Abdal Hakim provides an important tool for the students as they strive to form meaningful selves and careers in contemporary Britain. Thus, references to authentic Islam is used to support the development of both working and moral modern subjects.